Life-Threatening QT Prolongation in a Preterm Infant - Paech, Christian (AJP Rep, 2014)
Introduction Temporary QT-interval prolongation following intracranial hemorrhage and hydrocephalus has been repeatedly reported in adults. Case We report a case of excessive QT prolongation with sudden bradycardia resulting in 2:1 atrioventricular conduction in a preterm infant most likely associated with a congenital hydrocephalus. Pathomechanisms are discussed. Conclusion Congenital hydrocephalus predisposes to excessive QT prolongation in preterm infants.